2020
DOI: 10.1177/1745506520949727
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of obstructed labor among women attending intrapartum care in Amhara Region, Northwest Ethiopia: A hospital-based unmatched case–control study

Abstract: Objectives: maternal and neonatal mortality in Ethiopia is a major reproductive health problem. Obstructed labor is one of the leading causes of maternal, fetal, and neonatal morbidity in developing countries. The evidence regarding its determinants at the tertiary level of care is sparse. Therefore, this study aimed to study the determinants of obstructed labor among women attending intrapartum care in Amhara region referral hospitals. Methods: A Hospital-based unmatched case-control study was conducted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
(34 reference statements)
1
8
0
2
Order By: Relevance
“…In addition, the study also indicated that the higher odds of obstructed labour among women who reside within 10-50 kilometers compared to those who reside below 10 kilometers. This finding is in line with studies done in Tanzania [50] and Ethiopia [24,25]. This might be due to the fact that women living close to hospitals get life-saving obstetric information and services in labour earlier, reduce delays from referral and treatment, and reduce maternal morbidity.…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the study also indicated that the higher odds of obstructed labour among women who reside within 10-50 kilometers compared to those who reside below 10 kilometers. This finding is in line with studies done in Tanzania [50] and Ethiopia [24,25]. This might be due to the fact that women living close to hospitals get life-saving obstetric information and services in labour earlier, reduce delays from referral and treatment, and reduce maternal morbidity.…”
Section: Plos Onesupporting
confidence: 89%
“…However, studies showed that the burden of obstructed labour and its adverse maternal and perinatal outcomes appear to be high and remain a common challenge in Ethiopia [13,[17][18][19][20][21][22][23]. Different studies conducted across the countries showed that there were different determinants of obstructed labor such as, maternal age, maternal residence, women's education status, women's occupational status [24], distance from the hospital /health center, parity, antenatal visit, weeks of gestation at the first visit of antenatal care [24], age at first birth, fetal presentation, history of pregnancy-related complications and birth weight [13,19,25].…”
Section: Introductionmentioning
confidence: 99%
“…Among sixteen studies thirteen were cross sectional [1,14,[35][36][37][38][39][40][41][42][43][44][45] and three case-controls [46][47][48] in study design. Regarding the geographical area, six from Oromia [14,35,36,40,41,47], four [3,37,39,42] from Southern Nation Nationalities and People (SNNPR), and four [1,38,43,48] from Tigray region, two studies [45,46] were from Amhara region. Among the included studies the largest sample size was 13,425 [41], whereas the smallest was 90 [48] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Primarily, all three case-control [46][47][48] studies were not considered in the incidence estimation, because they did not report the incidence of obstructed labor, but all studies were included in factor analysis. The pooled incidence of obstructed labor is presented on a forest plot (Fig.…”
Section: Incidence Of Obstructed Labor In Ethiopiamentioning
confidence: 99%
“…According to the scientific facts, socio-demographic features, obstetric characteristics, and healthcare facility-related factors were shown to be associated with OL. The age of the mother, place of residence, and level of education were socio-demographic features associated with OL [ 1 , 4 , 21 – 24 ]. Based on obstetrical factors, gravidity, frequency of antenatal visits, and birth to big baby were all associated with OL [ 1 , 22 – 26 ].…”
Section: Introductionmentioning
confidence: 99%